Simple Fabrication of Flexible Biosensor Arrays Using Direct Writing for Multianalyte Measurement from Human Astrocytes - Nolan, James K. (SLAS Technol, 2019)
Simultaneous measurements of glucose, lactate, and neurotransmitters (e.g., glutamate) in cell culture over hours and days can provide a more dynamic and longitudinal perspective on ways neural cells respond to various drugs and environmental cues. Compared with conventional microfabrication techniques, direct writing of conductive ink is cheaper, faster, and customizable, which allows rapid iteration for different applications. Using a simple direct writing technique, we printed biosensor arrays onto cell culture dishes, flexible laminate, and glass to enable multianalyte monitoring. The ink was a composite of PEDOT:PSS conductive polymer, silicone, activated carbon, and Pt microparticles. We applied 0.5% Nafion to the biosensors for selectivity and functionalized them with oxidase enzymes. We characterized biosensors in phosphate-buffered saline and in cell culture medium supplemented with fetal bovine serum. The biosensor arrays measured glucose, lactate, and glutamate simultaneously and continued to function after incubation in cell culture at 37 °C for up to 2 days. We cultured primary human astrocytes on top of the biosensor arrays and placed arrays into astrocyte cultures. The biosensors simultaneously measured glucose, glutamate, and lactate from astrocyte cultures. Direct writing can be integrated with microfluidic organ-on-a-chip platforms or as part of a smart culture dish system. Because we print extrudable and flexible components, sensing elements can be printed on any 3D or flexible substrate.